The target tracking system design for the passive coherent locator - A. A. Konovalov (Известия высших учебных заведений России: Радиоэлектроника, 2015)
The target tracking system design for the passive coherent locator creating at Saint Petersburg electrotechnical university "LETI" are discussed. The variant of two-stage scheme is proposed as an original solution. In this scheme data association for confirmed and maintained tracks is fulfilled in bistatic coordinates and filtering on the track initiation and maintenance stages is made by nonlinear unscented Kalman filter initialized by two bistatic measurements.